2020
DOI: 10.3892/etm.2020.8670
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin improves diabetic coronary arterial vasomotor responsiveness by upregulating myocyte voltage‑gated K+ channels

Abstract: Hesperetin (HSP) is a naturally occurring flavonoid. The present study aimed to investigate the potential vasomotor effects and mechanisms of HSP action on rat coronary arteries (RCAs) injured by diabetes or high glucose concentrations. HSP (100 mg/kg/day) was intragastrically administered to the rats for 8 weeks, which were rendered diabetic with a single intraperitoneal injection of 60 mg/kg streptozotocin (STZ). The vascular tone of RCAs was recorded using a wire myograph. The voltage-dependent K + (Kv) cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In [ 94 ], it was reported that the chronic administration of hesperetin was able to increase the expression of Kv1.2 channels in coronary arterial smooth muscle cells of diabetic rats. The authors conclude that since the expression of these ion channels is lowered in the diabetic rats, hesperetin can be considered a promising therapeutic agent in the treatment of coronary arterial dysfunction resulting from diabetes.…”
Section: Kv Channelsmentioning
confidence: 99%
“…In [ 94 ], it was reported that the chronic administration of hesperetin was able to increase the expression of Kv1.2 channels in coronary arterial smooth muscle cells of diabetic rats. The authors conclude that since the expression of these ion channels is lowered in the diabetic rats, hesperetin can be considered a promising therapeutic agent in the treatment of coronary arterial dysfunction resulting from diabetes.…”
Section: Kv Channelsmentioning
confidence: 99%
“…69 Notably, recent investigation demonstrated that Hst significantly protects against diabetes-induced coronary artery dysfunction. Liu et al 70 demonstrated in vivo and in vitro that Hst restored the contraction-relaxation response in diabetic rat coronary arteries by increasing the expression of Kv channels in myocytes and reversing vasodilatory dysfunction in the rat coronary arteries. In addition, waterdispersible Hst has also been used to explore the protective effect on atherosclerosis progression in Apo-E KO mice.…”
Section: Hesperetin and Diabeticmentioning
confidence: 99%